Solving mould problems for automotive part (box lower) by using simulation software (Cadmould) / Mohd Syaiful Iman Tumijan - Tumijan, Mohd Syaiful Iman (2009)
The study was conducted to solve the mould problems for automotive part (Box Lower) using Cadmould simulation software. Box Lower parts for model BLM is simulate by using Cadmould. Cadmould is CAE software that uses to simulate plastic flow during injection moulding process. Box Lower is made by using General purpose 6523 Polypropylene Homopolymer producing by Lyondell Basell Montell. In the study the process parameter chosen were filling time, melt temperature and wall temperature. This parameter was varied and their effect on filling problem was simulated. Based on this study it was found that the process parameters can not solve the filling problem of the part. Beside that, the cooling channel and part thickness of the part was analyze to solve the filling problem. With the cooling system design the filling problem cannot solve the filling problem but with increase the part thickness the filling problem have been solve. The dimensions of the part thickness was not uniform due to the problem occur. Generally, it can be concluded that CAE simulation technique was useful to solve the filling problem in order to obtained perfect parts.